Taffic monitoring via satellite - Baumgartner, Stefan; Krieger, Gerhard (Positions, 2011)
Traffic monitoring from space, day and night, from more than 500 kilometers up above; is that possible? Indeed it is! At the DLR Microwaves and Radar Institute a special traffic processor for the German TerraSAR-X / TanDEM-X radar satellite constellation has been developed. With the traffic processer vehicles moving on open land and on open sea can be detected and their parameters geographical position, velocity and heading can be estimated. In the paper the principle of the traffic processor is explained and first measurement result are presented and discussed.
DLR Import::2019-04-02